Impacts of Duck-Origin Parvovirus Infection on Cherry Valley Ducklings From the Perspective of Gut Microbiota - Luo, Qihui; Xu, Jing; Huang, Chao; Lei, Xinyu; Cheng, Dongjing; Liu, Wentao; Cheng, Anchun; Tang, Li; Fang, Jing; Ou, Yangping; Geng, Yi; Chen, Zhengli (Frontiers in Microbiology, 2019)
Duck-origin goose parvovirus (D-GPV) is the causative agent of beak atrophy and dwarfism syndrome (BADS), characterized by growth retardation, skeletal dysplasia and persistent diarrhea. However, the pathogenic mechanism of D-GPV remains undefined. Here, we first reported the gut microbiome diversity of D-GPV infected Cherry Valley ducks. In the investigation for the influence of D-GPV infection on gut microbiota through a period of infection, we found that D-GPV infection caused gut microbiota dysbiosis by reducing the prevalence of the dominant genera and decreasing microbial diversity. Furthermore, exfoliation of the intestinal epithelium, proliferation of lymphocytes, up-regulated mRNA expression of pro-inflammatory TNF-α, IL-1β, IL-6, IL-17A and IL-22 and down-regulated mRNA expression of anti-inflammatory IL-10 and IL-4 occurred when D-GPV targeted in cecal epithelium. In addition, the content of short chain fatty acids (SCFAs) in cecal contents was significantly reduced after D-GPV infection. Importantly, the disorder of pro-inflammatory and anti-inflammatory cytokines was associated with the decrease of SCFAs-producing bacteria and the enrichment of opportunistic pathogens. Collectively, the decrease of SCFAs and the enrichment of pathogen-containing gut communities promoted intestinal inflammatory injury. These results may provide a new insight that target the gut microbiota to understand the progression of BADS disease and to research the pathogenic mechanism of D-GPV.